Pengaruh Efikasi Diri, Literasi Digital, dan Modal terhadap Niat Berwirausaha (Survei pada Mahasiswa Entrepreneur Program Studi Administrasi Bisnis UMMI Periode 2021-2022) - Milki Hamdan Yuwafi; Dicky Jhoansyah; Sopyan Saori (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rising number of educated unemployed graduates in Indonesia highlights the urgency of strengthening entrepreneurial intention among university students. Despite having academic qualifications, many graduates still prefer seeking formal employment rather than creating new businesses. This study aims to examine the effects of self-efficacy, digital literacy, and capital on entrepreneurial intention among students of the Entrepreneur Program in the Business Administration Study Program at Universitas Muhammadiyah Sukabumi during the 2021–2022 period. A quantitative approach was employed using a saturated sampling technique involving 96 students. Data were collected through structured online questionnaires measured using a Likert scale and analyzed using multiple linear regression with SPSS. The results indicate that self-efficacy has a positive and significant effect on entrepreneurial intention, suggesting that students with stronger confidence in their abilities are more inclined to engage in entrepreneurial activities. Digital literacy also shows a significant positive influence, emphasizing the importance of technological competence and critical information management in supporting entrepreneurial readiness. In addition, capital comprising financial, human, and social dimensions significantly affects entrepreneurial intention. Simultaneously, self-efficacy, digital literacy, and capital explain 93% of the variance in entrepreneurial intention. These findings support the Theory of Planned Behavior, particularly the role of perceived behavioral control in shaping entrepreneurial intention.